Correlation Luteinizing Hormone (LH)/Follicle Stimulating Hormone (FSH) Ratio with Low Density Lipoprotein (LDL)/ High Density Lipoprotein (HDL) Ratio in Polycystic Ovarium Syndrome (PCOS) Patients - Susi Oktaviani; Jusak Nugraha; Ashon Sa’adi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of this study is to analyze the correlation between the ratio of LH and FSH levels with LDL andHDL cholesterol in PCOS patients. This study is an observational cross-sectional study. The population inthis study were women newly diagnosed with polycystic ovary syndrome who came to RSIA Ferina, RSIALombok 22, Elizabeth Clinic and RSIA Putri Surabaya and Clinical Pathology Laboratory of dr. SoetomoSurabaya. Examination of FSH, LH and LDL and HDL cholesterol levels on 27 specimens (stored frozenserum) using the ICT (Accurate Intan Madya®, VEDALAB) and enzymatic colorimetric (Dimension EXL®,Siemens) methods. Statistical analysis was performed using the Spearman and Pearson correlation test,with a significance level of p <0.05. The results showed that there was a moderate positive correlationbetween FSH and LDL cholesterol (r = 0.491, p = 0.009). Phenotype D of PCOS (non-hyperandrogenictype) had a moderate negative correlation between the LH / FSH ratio and the LDL/HDL cholesterol levelratio (r = -0.487, p <0.05). However, there was no relationship between the LH/FSH ratio and the ratioof LDL/HDL cholesterol levels in all SOPK patients in this study. This study showed that phenotype DPCOS patients (non-hyperandrogenic type) were less likely to have cardiovascular complications than otherphenotypic PCOS patients. Insulin resistance has a role in the risk of dyslipidemia in non-hyperandrogenicPCOS patients.